Spontaneous formation and spatial self-organization of mechanically induced mesenchymal-like cells within geometrically confined cancer cell monolayers. (February 2022) - Lin, Feng; Zhou, Yuwei; Duan, Xiaocen; Fang, Xu; Zhang, Qing; Zhang, Yajun; Wang, Pudi; Huang, Jianyong
Abstract: There is spatiotemporal heterogeneity in cell phenotypes and mechanical properties in tumor tissues, which is associated with cancer invasion and metastasis. It is well-known that exogenous growth factors like transforming growth factor (TGF)-β, can induce epithelial-mesenchymal transition (EMT)-based phenotypic transformation and the formation of EMT patterning on geometrically confined monolayers with mechanics heterogeneity. In the absence of exogenous TGF-β stimulation, however, whether geometric confinement-caused mechanics heterogeneity of cancer cell monolayers alone can trigger the EMT-based phenotypic heterogeneity still remains mysterious. Here, we develop a micropattern-based cell monolayer model to investigate the regulation of mechanics heterogeneity on the cell phenotypic switch. We reveal that mechanics heterogeneity itself is enough to spontaneously induce the emergence of mesenchymal-like phenotype and asymmetrical activation of TGF-β-SMAD signaling. Spatiotemporal dynamics of patterned cell monolayers with mesenchymal-like phenotypes is essentially regulated by tissue-scale cell behaviors like proliferation, migration as well as heterogeneous cytoskeletal contraction. The inhibition of cell contraction abrogates the asymmetrical TGF-β-SMAD signaling activation level and the emergence of mesenchymal-like phenotype. Our work not only sheds light on the key regulation of mechanics heterogeneity caused by spatially geometric confinement on regional mesenchymal-like phenotype of cancer cell monolayers, but highlights the key role of biophysical/mechanical cues in triggering phenotypic switch.